Vestígios da dengue no anúncio e no jornal: dimensões acontecimentais e formas de experiência pública na (da) cidade - Rennan Lanna Martins Mafra (2011)
This doctoral thesis deals with the understanding of how printed materialities of communication of daily newspaper and government advertisement embody singular forms of public experience with the problem of dengue, in a city like Belo Horizonte. For this, weproduce a path of research that seeks to investigate 1) how such experience that is constituted by happening dimensions keep form by these materialities; 2) how such form - communication par excellence - is revealed through interaction practices and problematic fields in the midst of an urban way of living and support this public issue. For this, we built amethodological approach that takes the textualization experience of dengue in the newspaper and in the advertisement by a movement of distanciation epiphany (Gumbrecht, 2010; Ricoeur, 1991) that takes place from a case study (Braga, 2008), guided by the evidentiary paradigm (Braga, 2008; Ginzburg, 1991). With the aim of cutting and graspingthe reality of choice, the case study is supported from two investigation procedures: drift mapping (Silva et alii, 2008) and "ethnography" of texts (Certeau, 1994; Ricoeur, 1991; Canevacci, 1993). The result of this methodological combination turned the expression of a possible Map of Experiences - the stitching and the constellation mapping of certain units of strength (reciprocal paths, memory, strategy and others), the dominant crop in this research. The expression of such a map is, therefore, as an attempt to suggest a possible interaction path opened by evidence of dengue from happening dimensions and forms of public experience embodied in the printed newspaper and government advertisement in (of the) city of Belo Horizonte.